PENGARUH CORPORATE GOVERNANCE DAN KONSENTRASI KEPEMILIKAN TERHADAP DAYA INFORMASI AKUNTANSI - Andi Wawo (AkMen JURNAL ILMIAH, 2013)
The objective of this research will test the effect of corporate governance and concentrated ownership on the informativeness of accounting. Especially, this research will test the effect of independent commissioner and audit committee as corporate governance mechanism and concentrated ownership on the informativeness of accounting. Independent directors are proportion independent director in board of director. Audit committee is presence of independent audit, while ownership data are proportion of biggest shareholder in company. This research samples are public companies listed on the Indonesian Stock Exchange for the period in 5 years which is in period of 2003 to 2007 with exception of bank and financial institutions. Hypothesis test by method which is used by Fang and Wong (2002) with independent variable consist of independent directors, audit committee and concentrate ownership, while control variable in this research use market to book ratio, leverage, and fixed effect. The result research can be summarized as following; The immediate of concentrated ownership at cut-off 10% as moderating variable on associated between independent commissioner and the informativeness of accounting can not support but associated between audit committee and the informativeness of accounting can support.